A simple procedure for fabricating graphene or modified graphene polyaniline composites for supercapacitor application. (2023) - Benny, Anish; George, Soney C.; Sankar, Vinu
Abstract: The depleting fuel resources and elevated air pollution are raising serious concerns among the global population. The fuel prices are also increasing day by day. Hence the world is more focused on maximizing conventional energy resources like solar, tidal, wind energies, etc. However, for the fullest utilization of conventional energy sources, we need efficient energy storage systems, and currently, we are using batteries as the primary energy storage elements. Nowadays, researchers are giving utmost importance to the development of supercapacitors. Graphene coming under carbon groups and polyaniline (PANI), coming under electronic conducting polymers (ECP), are two different materials mainly used for supercapacitor electrode fabrication. The normal route for synthesizing graphene-PANI composites is a time-consuming process. Here we present a simple route for synthesizing graphene-PANI composites. The same method can be adopted for fabricating modified graphene-PANI composites too. The FTIR, Raman spectroscopy, XRD, SEM, and TEM results showed that the formation of graphene-PANI composites in the current route is the same as that of the normal method. Moreover, the cyclic voltammetry (CV) and charge–discharge (CD) tests revealed excellent electrochemical performance and cyclability. The CV study reported that the specific capacitances of the supercapacitor are 235, 179, 120, 85, and 55 F/g at scan rates of 10, 20, 50, 100, and 200 mV/s. The capacitance retention ratio was more than 90% and the ESR was found to be 10.5 O.